An exploration of organizational expectations of different generations of employees during change - Kawana, Susan Mulemwa (Rhodes University, Faculty of Commerce, Rhodes Business School, 2020)
The aim of this study is to investigate the organizational expectations of different generations of employees at the Ministry of Finance's Inland Revenue and Customs and Excise Departments of the Republic of Namibia, which are undergoing organizational change processes. The different generations that were included in this study are Baby Boomers, Generation X, and Generation Y. The study explores the different expectations that the generations have in relation to the changes, in terms of leadership style and communication preferences. This study followed a qualitative approach. Quota sampling was used to select twelve participants for the study. The case study was carried out within a postpositivism paradigm. Data was collected by administering semi-structured, face-to-face interviews. The findings of the study indicate that there are generational differences in respect of preferred leadership styles and communication methods during organizational change. Baby Boomers and Generation X preferred a relationshiporiented leadership style, while generation Y preferred a visionary leadership style. Task-oriented leadership style was not the preferred style of any generation. Rather, in the midst of change, it seems there is a preference for relational leadership across all the Generations. In respect of communication, Baby Boomers preferred face-toface methods, Generation X preferred face-to-face and e-mail methods as sources of change communication, while Generation Y preferred a combination of communication methods. In the midst of change, it seems there is a common preference for face-to-face communication across all the Generations. Furthermore, employees generally did not feel ready for the changes. In the light of these findings, recommendations were made to guide change initiatives amongst employees of various generations. The limitations of the study were its sample size and focus on the public sector. For future research, a larger sample could be selected from all regional offices. Similar research can also be done in the private sector. The findings of the study provide an understanding of the experiences and expectations of different generations of employees during organizational change, and contribute to the body of knowledge on generational differences, readiness for change and the management of different generations as different stakeholders.
Keywords: Organizational change -- Psychological aspects; Organizational behavior -- Namibia -- Case studies; Employees -- Psychology -- Namibia; Organizational change -- Namibia -- Case studies; Intergenerational relations -- Namibia; Namibia. Inland Revenue Directorate; Namibia. Customs and Excise